2009
DOI: 10.1002/app.31345
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrochemical capacitance of poly(pyrrole‐co‐aniline)

Abstract: The copolymer of pyrrole and aniline, poly(pyrrole-co-aniline), has been prepared by chemical oxidation of corresponding monomer mixtures with ammonium peroxysulfate. Techniques of FTIR, SEM-EDS, and BET surface area measurement were used to characterize the structure and morphology of the copolymer. The electrochemical properties of the copolymer were investigated by cyclic voltammetry, galvanostatic charge-discharge, and electrochemical impedance spectroscopy. The results indicated that poly(pyrrole-co-anili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The copolymerization of aniline and pyrrole monomers not only offers a possibility to combine superior properties of the individual monomers but also exhibits new properties such as thermal stability better than PANi and PPy [2, 20-25]. Furthermore, it has been demonstrated that poly(aniline-co-pyrrole) (PANi-co-PPy) exhibited better electrochemical capacitive performance than single component [2,21,22,26]. However, it is also observed that the conductivity decreased when aniline is polymerized with pyrrole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copolymerization of aniline and pyrrole monomers not only offers a possibility to combine superior properties of the individual monomers but also exhibits new properties such as thermal stability better than PANi and PPy [2, 20-25]. Furthermore, it has been demonstrated that poly(aniline-co-pyrrole) (PANi-co-PPy) exhibited better electrochemical capacitive performance than single component [2,21,22,26]. However, it is also observed that the conductivity decreased when aniline is polymerized with pyrrole.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical supercapacitors that provide a bridge between conventional capacitors with short charge-discharge times and batteries with long discharge times have attracted much attention due to their excellent cycling performance, higher power density, fast response, and potential application in electric vehicles, consumer electronics, and other devices [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…(1/1) copolymer after 25 cycles of CV scans at a scan rate of 50 mV s [16]. It is believed that the best practice test methods accurately predicting a material's supercapacitor performance is from a two electrode system [17].…”
Section: Introductionmentioning
confidence: 99%
“…To measure the electrical properties of PAZ and PAPZ, nanocomposites were pressed on a graphite electrode (1 cm 2 ) by the method described in Ref. and used as a working electrode. To test the properties of EP, EPAZ, and EPAPZ coatings using EIS, SS304 plates with these coatings were used as working electrodes.…”
Section: Methodsmentioning
confidence: 99%